Factors Affecting the Improvement of the Economic Status of Corn Farmers (Case Study of Corn Farmers in Suka Damai Village, Lawe Sigala-Gala District, Southeast Aceh District) - Zesi Mardi; Syahbudin Hasibuan; Ahmad Rafiki (Journal of Social Research, 2023)
This study aims to find out the factors that influence the increase in the economic status of corn farmers in Sukadamai Village, Lawe Sigala Gala District. The researchers' considerations for choosing this area are because Lawe Sigala Gala District is a corn production center with the second highest productivity after Lauser District, this study uses a Quantitative approach, in this study the total population is the entire Association of Farmers Group named Gapoktan Kembang Bersama, totaling 65 people, the sample used is a saturated sample where all the population is used as a sample. The data analysis technique used is multiple linear regression analysis. As for the results of this study, a constant value of 4,529 indicates the value of the independent variables consisting of Corn Production, Capital, Planning, Human Resources, and Technology. If there is a change, it will increase the economic status of the Sukadamai community by 45.29%. Partially the independent variables consisting of Technology, Human Resources, Planning, Corn Production, and Capital have a significant effect on the economic status of the Sukadamai community because the value of t count > t table and a significant level of <0.05. In the study, the independent variables consisting of Technology, Human Resources, Planning, Corn Production, and Capital had a significant effect on the economic status of the Sukapeace community, because the value of f count > f table (29,819 > 2.37) and a significant level of 0.000 <0.05. R Square value of 0.716 or 71.6% contribution of the variable Technology, HR, planning, Corn Production, and Capital to economic status while the remaining 23.4% is influenced by other factors not examined in this study.